Archaeology of Empire in Achaemenid Egypt - Colburn, Henry P. (Edinburgh)
xix, 318 sayfa, [2] sayfa harita
Keywords: “A study of the material culture of Egypt during the period of Achaemenid Persian rule, c. 526-404 BCE. Previous studies have characterised Achaemenid rule of Egypt either as ephemeral and weak or oppressive and harsh. These characterisations, however, are based on the perceived lack of evidence for this period, filtered through ancient and modern preconceptions about the Persians. Henry Colburn challenges these views by assembling and analyzing the archaeological remains from this period, including temples, tombs, irrigation works, statues, stelae, sealings, drinking vessels and coins. By looking at the decisions made about material culture - by Egyptians, Persians and others - it becomes possible to see both how the Persians integrated Egypt into their empire and the full range of experiences people had as a result.” --